Гнездование осы Gymnomerus laevipes (Hymenoptera, Vespidae) в Крыму - Фатерыга, А.В. (Вестник зоологии, 2012)
Изучены гнёзда Gymnomerus laevipes (Shuckard, 1837) в полостях стеблей тростника и ежевики. Гнёзда содержат от 2 до 14 ячеек (в среднем — 7), соотношение полов сдвинуто в сторону самок (1,9 ♀ на 1 ♂). Приведены данные по размерным параметрам заселенных полостей, размерам ячеек, массе ячеек и предкуколок, построена статистическая модель гнезда. Ячейки гнёзд G. laevipes отнесены к типу полнокомпонентных гетероморфных ячеек, их длина обратно пропорционально связана с диаметром гнездового канала. Самка G. laevipes подвешивает яйцо на боковую стенку ячейки возле её дна. В качестве провизии осы заготавливают личинок жуков-долгоносиков Phytonomus variabilis. G. laevipes — моновольтинный вид, зимует предкуколка в плотном однослойном коконе. Имаго выходят из ячеек гнёзд в последовательности, обратной их закладке. Гнёзда поражают: паразитоид Hoplocryptus melanocephalus (Hymenoptera, Ichneumonidae), хищник Trichodes apiarius (Coleoptera, Cleridae) и инквилины Chrysis rutilans (Hymenoptera, Chrysididae) и Amobia signata (Diptera, Sarcophagidae). The nests of Gymnomerus laevipes (Shuckard, 1837) disposed in the hollow stems of reed and bramble were studied. The nests contain from 2 to 14 cells (7 in average), sex ratio is female-biased (1.9 ♀ to 1 ♂). The data on dimensional parameters of nest cavities, measurements of cells, mass of cells and prepupae were given; nest statistical model was constructed. The cells of G. laevipes nests a considered to belong to the type of full-component heteromorphic cells; their lengths are found to be inversely proportional to the diameter of the nest hollow. Female of G. laevipes attach its egg on the lateral wall of the cell near its bottom. Alfalfa weevil (Phytonomus variabilis) larvae were collected by females as the victuals. G. laevipes is monovoltine species; prepupae hibernate in dense one-layer cocoon. Adults leave the nest cells in sequence, reverse to sequence of cells laying. Nests were damaged by a parasitoid Hoplocryptus melanocephalus (Hymenoptera, Ichneumonidae), predator Trichodes apiarius (Coleoptera, Cleridae) and inquilines Chrysis rutilans (Hymenoptera, Chrysididae) and Amobia signata (Diptera, Sarcophagidae).